2007 IEEE/RSJ International Conference on Intelligent Robots and Systems 2007
DOI: 10.1109/iros.2007.4399424
|View full text |Cite
|
Sign up to set email alerts
|

Performance benefits of self-assembly in a swarm-bot

Abstract: Abstract-Mobile robots are said to be capable of selfassembly when they can autonomously form physical connections with each other. Despite the recent proliferation of selfassembling systems, little work has been done on using selfassembly to add functional value to a robotic system, and even less on quantifying the contribution of self-assembly to system performance.In this study we demonstrate and quantify the performance benefits of i) acting as a physically larger self-assembled entity, ii) using self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…This model was then demonstrated by Kube and Bonabeau with experiments involving a group of real robots [11]. Additional experiments have shown that transport performance grows in a super linear way with the number of robots, which is similar to what is observed with ants [12,13].…”
Section: Introductionsupporting
confidence: 56%
“…This model was then demonstrated by Kube and Bonabeau with experiments involving a group of real robots [11]. Additional experiments have shown that transport performance grows in a super linear way with the number of robots, which is similar to what is observed with ants [12,13].…”
Section: Introductionsupporting
confidence: 56%
“…How to design a swarm system that can meet the requirements of 3-D manipulation tasks is an open problem, in particular, if the requirements are not known in advance. Such systems might benefit from a tight coupling between behaviour and morphology (Pfeifer and Bongard, 2006;O'Grady et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…During the last 50 years, a variety of self-assembling systems were developed and used to design and analyze processes exhibiting a range of elementary functions. Ongoing work continues the study of such processes and functions, in particular, those of formation [6], [20], [39], [63], [71], growth [49], [85], [86], self-reconfiguration [76], [77], [121], self-repair [117], and template replication [131].…”
Section: Achievements and Future Directionsmentioning
confidence: 99%